2006
DOI: 10.1212/01.wnl.0000198253.35119.83
|View full text |Cite
|
Sign up to set email alerts
|

Clinically isolated syndromes

Abstract: The presence of oligoclonal IgG bands is highly specific and sensitive for early prediction of conversion to multiple sclerosis. MRI criteria have a high specificity but less sensitivity. The simultaneous use of both tests shows high sensitivity and specificity in predicting clinically isolated demyelinating syndrome conversion to clinically definite multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(68 citation statements)
references
References 16 publications
7
57
1
3
Order By: Relevance
“…Ninety four per cent of these patients presented CSF OCB at the time of the first relapse, meaning that the association of CIS and their presence could increase to 9 times the risk of CDMS conversion. Masjuan and colleagues 18 demonstrated that CSF OCB had 91.4% sensitivity and 94.1% specificity in CIS conversion to MS, which was superior to the prediction associated to abnormal brain MRI 19 . The CSF examination may show evidence of inflammatory activity during relapses as slight elevation of mononuclear white blood cells (pleocytosis) with cell counts varying between 5 to 50 cells/ mm3 in one third of MS cases.…”
Section: Introductionmentioning
confidence: 97%
“…Ninety four per cent of these patients presented CSF OCB at the time of the first relapse, meaning that the association of CIS and their presence could increase to 9 times the risk of CDMS conversion. Masjuan and colleagues 18 demonstrated that CSF OCB had 91.4% sensitivity and 94.1% specificity in CIS conversion to MS, which was superior to the prediction associated to abnormal brain MRI 19 . The CSF examination may show evidence of inflammatory activity during relapses as slight elevation of mononuclear white blood cells (pleocytosis) with cell counts varying between 5 to 50 cells/ mm3 in one third of MS cases.…”
Section: Introductionmentioning
confidence: 97%
“…This study had been approved by ethical committee of Al-Jadaani and Bugshan Hospitals. Patients who diagnosed MS, Table 1: Proposed diagnostic criteria for radiologically isolated syndrome [5].…”
Section: Methodsmentioning
confidence: 99%
“…According to the 2017 revision of McDonald criteria, including two major changes, irst is the early diagnosis of MS in patients with CIS with dissemination in space and +ve OCBs, without waiting for dissemination in time, second is, symptomatic or asymptomatic MRI lesions (except those in the optic nerve) can be considered as dissemination in space or time [4]. Incidental MR imaging indings resembling MS without typical MS symptoms are termed RIS, it was introduced in 2009 by Okuda to categorize incidental WM lesions suggestive of demyelinating disease in patients without typical MS symptoms and no better explanation for the MR imaging anomalies [5]. CSF analysis was one of the main paraclinical diagnostic criteria for MS (it is mandatory in the 2017 revision of McDonald criteria for MS); nowadays, it is of great importance in differential diagnosis of MS [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported that the presence of oligoclonal IgG bands is highly specific and sensitive for early prediction of conversion to MS 20 . In this last paper, the authors emphasized that the simultaneous use of both tests shows high sensitivity and specificity in predicting clinically isolated demyelinating syndrome conversion to clinically definite MS.…”
Section: Figure Risk Of Conversion From Cis To Cdmsmentioning
confidence: 99%